Dendrobium fimbriatum Hook polysaccharide ameliorates dextran-sodium-sulfate-induced colitis in mice via improving intestinal barrier function, modulating intestinal microbiota, and reducing oxidative stress and inflammatory responses. Issue 1 (7th December 2021) - Wang, Yu-Jing; Li, Qiang-Ming; Zha, Xue-Qiang; Luo, Jian-Ping
Abstract : The ameliorative effect of Dendrobium fimbriatum polysaccharide (cDFPW1) on ulcerative colitis (UC) was investigated using a dextran-sodium-sulfate-induced (DSS-induced) mouse model in the present study. Abstract : The ameliorative effect of Dendrobium fimbriatum polysaccharide (cDFPW1) on ulcerative colitis (UC) was investigated using a dextran-sodium-sulfate-induced (DSS-induced) mouse model in the present study. The results showed that cDFPW1 effectively improved colitis in mice by ameliorating weight loss, disease activity index (DAI) and colonic pathological damage, and by protecting the intestinal barrier function integrity. Moreover, cDFPW1 modulated the composition and metabolism of intestinal microbiota through enhancing Romboutsia, Lactobacillus and Odoribacter, and reducing Parasutterella, Burkholderia-Caballeronia-Paraburkholderia and Acinetobacter in colitis mice. Notably, cDFPW1 significantly restored the homeostasis of Th17/regulatory T (Treg) cells and the expression of specific cytokines. Western blotting of colon tissues showed that cDFPW1 markedly up-regulated the expression of Nrf2 and inhibited the phosphorylation of NF-κB signaling. These results indicated that cDFPW1 possesses the potential of improving UC and its effect on palliating colitis may be connected with the regulation of Nrf2/NF-κB signaling.